Analisis Resolusi Konflik Agraria di Kabupaten Jember Berdasarkan Perspektif Keadilan Sosial - Hastuti, Dwi; Karya Pamungkas, Teguh (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam Jember, 2025)
Jember Regency often faces agrarian conflicts involving communities and plantation companies. Various efforts to resolve the conflict have been made, but have not yet fully provided satisfactory results for all parties. Therefore, an in-depth analysis of the resolution of agrarian conflicts in Jember Regency is very important. The purpose of this study is to reveal the root causes of agrarian conflicts in Jember, evaluate the effectiveness of various conflict resolution approaches that have been taken, and develop an approach to conflict resolution based on social justice. This research is an empirical legal research using the Sociology of Law approach, the techniques used are interviews, documentation and observation. Then the inductive data analysis technique and based on empirical facts or field conditions. The results of this study indicate that the root of the problem of agrarian conflict in Jember Regency is due to factors of need, land as a cultural identity of the community, and the positions of the conflicting parties that are not in harmony. Efforts to resolve agrarian conflicts in Jember Regency continue to be carried out through mediation. The BPN, Regent and DPRD act as mediators. It's just that the failure of efforts to resolve agrarian conflicts in Jember Regency is due to the asymmetry of power and differences in interests between the conflicting parties. The approach to agrarian conflict resolution in Jember Regency from a social justice perspective needs to consider a participatory approach in conflict mediation that is free of interests and increases access and legal certainty.